Pengembangan Buku Ajar Matematika dengan Pendekatan Contextual Teaching And Learning (CTL) pada Materi Statistika untuk Siswa Kelas XI SMK Bisnis dan Manajemen - Muzakki Tamami; Vera Maya Santi; Tian Abdul Aziz (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
This study aims to produce teaching materials in the form of mathematics textbooks for class XI students at SMKN 48 Jakarta majoring in Business and Management. This mathematics textbook was made due to students' lack of understanding of mathematics material. This is reinforced by the results of an analysis of the needs of students at SMKN 48 Jakarta majoring in Business and Management, namely 86.11% of students stated difficulties in learning mathematics. Based on the analysis of students' needs, as many as 22.71% of students chose statistics as material that was considered difficult, so the material to be developed was statistics material. This research and development uses the Research and Development method which refers to the Borg & Gall model. The mathematics textbook developed has been validated by material and language experts with an average percentage value of 82.96% in the very good category, and media expert validation with an average percentage value of 91.78% in the very good category. Then trials were carried out on teachers and students. In the teacher evaluation results obtained an average percentage value of 91.87% in the very good category. In the results of the small-scale student trials, an average percentage value of 89.92% was obtained in the very good category and the large-scale student trials obtained an average percentage value of 83.64% in the very good category. So that the developed mathematics learning video is feasible to be used in the learning process at school with an overall average of 88.03%. Â Penelitian ini bertujuan untuk menghasilkan bahan ajar berupa buku ajar matematika untuk siswa kelas XI di SMKN 48 Jakarta jurusan Bisnis dan Manajemen. Buku ajar matematika ini dibuat karena kurangnya pemahaman siswa terhadap materi matematika. Hal tersebut diperkuat oleh hasil analisis kebutuhan siswa di SMKN 48 Jakarta jurusan Bisnis dan Manajemen, yaitu 86,11% siswa menyatakan kesulitan dalam mempelajari matematika. Berdasarkan analisis kebutuhan siswa, sebanyak 22,71% siswa memilih statistika sebagai materi yang dianggap sulit, sehingga materi yang akan dikembangkan adalah materi statistika. Penelitian dan pengembangan ini menggunakan metode Research and Development yang mengacu pada model Borg & Gall. Buku ajar matematika yang dikembangkan telah melalui validasi ahli materi dan bahasa dengan nilai persentase rata-rata sebesar 82,96% dengan kategori sangat baik, dan validasi ahli media dengan nilai persentase rata-rata sebesar 91,78% dengan kategori sangat baik. Kemudian dilakukan uji coba kepada guru dan siswa. Pada hasil evaluasi guru diperoleh nilai persentase rata-rata sebesar 91,87% dengan kategori sangat baik. Pada hasil uji coba siswa skala kecil diperoleh nilai persentase rata-rata sebesar 89,92% dengan kategori sangat baik dan uji coba siswa skala besar diperoleh nilai persentase rata-rata sebesar 83,64% dengan kategori sangat baik. Sehingga video pembelajaran matematika yang dikembangkan layak untuk dimanfaatkan dalam proses pembelajaran di sekolah dengan rata-rata keseluruhan sebesar 88,03%.